Dynamic variation of non-structural carbohydrates in branches and leaves of temperate broad-leaved tree species over a complete life history - Wang, Kaibo; Jin, Guangze; Liu, Zhili (Frontiers in Forests and Global Change, 2023)
The composition of non-structural carbohydrates (NSC), one of the photosynthetic products of plants, reflects the survival strategy of a plant. Although several studies have investigated variation of NSC content in woody plants over a set time scale, few studies have considered the dynamic variation of NSC over a continuous life history. In this study, the leaves, new twigs, and old branches of seven temperate broad-leaved tree species (diffuse-porous species: Betula platyphylla, Betula costata, Tilia amurensis, Acer pictum subsp.mono; ring-porous species: Ulmus davidiana var. japonica, Ulmus laciniata, Fraxinus mandshurica) were observed at three life history stages (seedling, sapling, and mature tree) to measure the dynamic changes of NSC and its influencing factors throughout the entire life cycles of these species. The results showed that life history, wood type and environmental factors (soil nitrogen and phosphorus content) significantly affected the NSC content in leaves and branches (including both new twigs and old branches). As plants grew, the NSC content in the leaves and branches generally showed an upward trend, meaning the total non-structural carbohydrate (TNC) content and soluble sugar (SS) content increased significantly, and the starch (ST) content was relatively stable. There were differences in NSC content between leaves and branches. The SS and TNC contents were mostly higher in branches than in leaves, while the ST content was mostly higher in leaves than in branches. The NSC content was higher in the leaves of the diffuse-porous species than of the ring-porous species, while it was lower in the branches of the diffuse-porous species than of the ring-porous species. Lastly, there was no significant difference in NSC content between the canopy layers of mature trees. This indicates that the influence of life stage on NSC content in leaves and branches of plants may be dominated by genetics instead of being regulated by light factors.